Niphargus diadematus sp. n. (Crustacea, Amphipoda, Niphargidae), an inhabitant of a shallow subterranean habitat in South Moravia (Czech Republic) - Hudec, Igor; Fišer, Cene; Dolanský, Jan (Zootaxa, 2017)
We present a subterranean amphipod from genus Niphargus collected in soil traps. Traps were set for sampling soil spiders in the inundation of the Včelínek Brook, Dyje River watershed, Czech Republic. Most likely, the species lives in a shallow subterranean habitat and has likely got entrapped into soil traps at elevated level of groundwater during two floods. In total 189 specimens were collected. The collected amphipods are small, slender and resemble species that were broadly classified to N. aquilex aggregate. Although damaged DNA does not allow more inclusive taxonomic and phylogenetic examination of the species, a comprehensive revision of 19 morphological diagnostic traits for 64 species from the aggregate indicates that these specimens should be treated as a new species, named Niphargus diadematus sp. n.